2020
DOI: 10.1002/jat.4057
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical modifications of model and native membranes of human immune cells in response to the action of zinc oxide nanoparticles

Abstract: The development of nanotechnology has led to the increased production of zinc oxide nanoparticles (ZnO‐NPs) and their application in a wide variety of everyday products. It creates the need for a full assessment of their safety for humans. The aim of the study was to assess the toxic effects of ZnO‐NPs on model human cells of the immune system: U‐937, HL‐60, HUT‐78, and COLO‐720L. Particular attention was paid to the direct interaction of the nanoparticles with membrane lipids and the role of zinc ions in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…A mixture consisting of pure phospholipids, reflecting the composition of the natural membranes HL-60 and U-937, was adopted as the control system. The shapes of these isotherms are typical for the studied models and can be found in the literature [28]. Previous studies performed on the HL-60 and U-937 cell lines suggested a higher sensitivity, identified for HL-60 line, in contrast to the U-937 line.…”
Section: Ftx Interaction With Multicomponent Monolayerssupporting
confidence: 56%
“…A mixture consisting of pure phospholipids, reflecting the composition of the natural membranes HL-60 and U-937, was adopted as the control system. The shapes of these isotherms are typical for the studied models and can be found in the literature [28]. Previous studies performed on the HL-60 and U-937 cell lines suggested a higher sensitivity, identified for HL-60 line, in contrast to the U-937 line.…”
Section: Ftx Interaction With Multicomponent Monolayerssupporting
confidence: 56%
“…The concentration of ZnO‐NPs in the body will be lower than the concentration at the point of contact. Therefore, the amounts applied for the present studies were much lower than those usually used in industry (Czyzowska, Dyba, Rudolphi‐Szydło, & Barbasz, 2020). That is why the results show a real threat not only associated with the use of products containing ZnO‐NPs but primarily with work in their production (Lu, Huang, Chen, Chiueh, & Shih, 2015; Ruszkiewicz et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…However, they suggest that although intracellular growth of ROS level correlates with cell viability, it was not a major factor in the cytotoxicity of ZnO particles, but only the response of cells to mitochondrial damage induced by zinc ions and ZnO particles. However, in our previous work, we showed that zinc ions are not the main factor causing the toxicity of zinc oxide nanoparticles toward cells of the immune system (Czyżowska et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…We presented the physicochemical characteristics in ultrapure water, phosphate‐buffered saline (PBS), and complete cell culture medium, of selected NPs earlier (Czyżowska et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we showed that commercial ZnO‐NPs are toxic to human immune cells, and the mechanism of their toxicity is related to the change in the composition and structure of the membranes of the studied cells (Czyżowska & Barbasz, 2020b; Czyżowska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%